2008
DOI: 10.1007/s10482-008-9268-5
|View full text |Cite
|
Sign up to set email alerts
|

Yeasts and filamentous fungi carried by the gynes of leaf-cutting ants

Abstract: Insect-associated microbes exhibit a wide range of interactions with their hosts. One example of such interactions is the insect-driven dispersal of microorganisms, which plays an essential role in the ecology of several microbes. To study dispersal of microorganisms by leaf-cutting ants (Formicidae: Attini), we applied culture-dependent methods to identify the filamentous fungi and yeasts found in two different body parts of leaf-cutting ant gynes: the exoskeleton and the infrabuccal pocket. The gynes use the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
65
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 49 publications
1
65
3
Order By: Relevance
“…Cladosporium fungi are phytopathogens [26] and may be transported by various insects causing their death. In a study of leaf-cutting queen ants, the Cladosporium fungus was prevalent in Atta laevigata and in A. capiguara [27]. It is believed that these fungi are frequently found due to their cosmopolitan distribution, being acquired from the environment and dispersed during the founding of a colony by queens or forage worker ants carrying leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Cladosporium fungi are phytopathogens [26] and may be transported by various insects causing their death. In a study of leaf-cutting queen ants, the Cladosporium fungus was prevalent in Atta laevigata and in A. capiguara [27]. It is believed that these fungi are frequently found due to their cosmopolitan distribution, being acquired from the environment and dispersed during the founding of a colony by queens or forage worker ants carrying leaves.…”
Section: Discussionmentioning
confidence: 99%
“…This neighborhood includes some study areas where Escovopsis was previously found: in a small colony of Rodrigues et al (2014) and in another work (NS Nagamoto et al, unpublished data), it was demonstrated that one of the colonies studied by Pagnocca et al (2008), denominated "Atta capiguara colony 1", was indeed infected with this parasite. Additionally, based on the long persistence of these ants' colonization in these areas (NS Nagamoto, personal obs.…”
Section: Methodsmentioning
confidence: 90%
“…On the other hand, a second study evaluated the integument and fungal pellets of gynes collected immediately before the mating flight (when gynes were leaving the parental colony). Although, Pagnocca et al (2008) used a larger sampling size in comparison to the Currie et al's (1999) study (Table 1) only one colony of Atta laevigata F. Smith and two colonies of Atta capiguara Gonçalves were sampled, in Brazil. In addition, the variation of Escovopsis prevalence between ant species and locations are aspects that prompt for additional studies to extend the existing data on the mode of transmission of this parasite (Currie, 2001a;Yek et al, 2012).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Microorganisms within this microbiota include: asexual fungi (Rodrigues et al 2005a,b;Pinto-Tomás et al 2009;Ribeiro et al 2012), yeasts (Carreiro et al 1997;Pagnocca et al 2008) and bacteria (Haeder et al 2009). Functionally, they include symbionts, saprotrophs, entomopathogens and pathogens of Leucoagaricus spp.…”
Section: I�����������mentioning
confidence: 99%